FREE NUTRITIOUS MEALS AS A STRATEGY FOR INCLUSIVE GREEN DEVELOPMENT: SYNERGY OF NUTRITION POLICY, HUMAN RESOURCE DEVELOPMENT, AND POVERTY ALLEVIATION IN INDONESIA - Hastuti Handayani Harahap; Frederick Rudy Sentosa Rajagukguk; Indra Welly Arifin (CV. Radja Publika, 2025)
Nutritional inequality and poverty remain structural problems that impact the quality of human resources and sustainable development in Indonesia. The Free Nutritional Meal Program (PMBG) is a strategic government policy aimed not only at improving the nutritional status of the community, particularly children and vulnerable groups, but also at supporting the development of high-quality and competitive human resources. This study aims to analyze the role of PMBG in improving community nutritional status, encouraging human resource development, and realizing synergies between nutrition policies, poverty alleviation, and inclusive green economic development. The research method used is a qualitative approach through literature review of various scientific studies, policy reports, and international publications. The results show that PMBG has great potential to improve the quality of community health and cognition, increase future workforce productivity, and create an economic multiplier effect through the involvement of MSMEs and the sustainable local agricultural sector. However, the implementation of this program also faces challenges, such as budget constraints, cross-sector coordination, and the sustainability of an environmentally friendly food supply chain. Therefore, optimizing PMBG as an inclusive green development strategy requires strengthening governance, integrating cross-sector policies, and active participation of local communities and businesses to provide long-term impacts on human development and the green economy in Indonesia.